2019
DOI: 10.48550/arxiv.1909.09443
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Convex Optimization Approach for Finite-Thrust Time-Constrained Cooperative Rendezvous

Boris Benedikter,
Alessandro Zavoli,
Guido Colasurdo

Abstract: This paper presents a convex approach to the optimization of a cooperative rendezvous, that is, the problem of two distant spacecraft that simultaneously operate to get closer. Convex programming guarantees convergence towards the optimal solution in a limited, short, time by using highly efficient numerical algorithms. A combination of lossless and successive convexification techniques is adopted to handle the nonconvexities of the original problem. Specifically, a convenient change of variables and a constra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…(Lu and Liu, 2013;Liu and Lu, 2014) showed that fast and reliable trajectory optimization is still possible in this case, by applying the same lossless convexification as in Problem 63 to the constraints (65c) and (65d) and successively linearizing the dynamics (65b). (Benedikter et al, 2019b) further proposed a filtering technique for updating the linearization reference point to improve the algorithm robustness. The advantage of this approach is its compatibility with general Keplerian orbits and perturbations like J 2 harmonic and aerodynamic drag.…”
Section: Rendezvous and Proximity Operationsmentioning
confidence: 99%
“…(Lu and Liu, 2013;Liu and Lu, 2014) showed that fast and reliable trajectory optimization is still possible in this case, by applying the same lossless convexification as in Problem 63 to the constraints (65c) and (65d) and successively linearizing the dynamics (65b). (Benedikter et al, 2019b) further proposed a filtering technique for updating the linearization reference point to improve the algorithm robustness. The advantage of this approach is its compatibility with general Keplerian orbits and perturbations like J 2 harmonic and aerodynamic drag.…”
Section: Rendezvous and Proximity Operationsmentioning
confidence: 99%